CFD study of drag and lift of sepak takraw ball at different face orientations - Mubin, A.S.A.; Ahmad, N.; Mamat, A.; Taha, Z.; Hasanuddin, I. (SAGE Publications Inc, 2015)
There have been a significant number of researches on computational fluid dynamic (CFD) analysis of balls used in sports such as golf balls, tennis balls, and soccer balls. Sepak takraw is a high speed court game predominantly played in Southeast Asia using mainly the legs and head. The sepak takraw ball is unique because it is not enclosed and made of woven plastic. Hence a study of its aerodynamics would give insight into its behaviour under different conditions of play. In this study the dynamics of the fluid around a static sepak takraw ball was investigated at different wind speeds for three different orientations using CFD. It was found that although the drag did not differ very much, increasing the wind velocity causes an increase in drag. The lift coefficient varies as the velocity increases and does not show a regular pattern. The drag and lift coefficients are influenced by the orientation of the sepak takraw ball.